Brand Formation and Branding: Choice of Strategies and their Evaluation - Grundey, Dainora (Ekonomika, 2002)
Having analysed the aspects of brands and branding terminology, it can be generalised that the formation and development of a company’s brand depend upon the following factors:(1) internal and external criteria of the enterprise’s environment,(2) customers and satisfaction of their expectations,(3) nature of products,(4) feasible choice of strategies in market and branding.Thus, the author has applied a three-fold approach in researching the scientific problem identified, namely, by:(1) analysing factors, influencing brand formation,(2) studying organisational aspects of brand formation in an enterprise,(3) presenting branding strategies and the evaluation of their alternative application in practice with examples from global and Lithuanian businesses.The attention is drawn to untraditional interpretation of brands with specification to L. K. Keller’s (1999) study “Brand Mantras: Rationale, Criteria and Examples”, where special mantras (i.e. certain wordings and phrases) are used to attract customers attention to certain brand names. The global examples come from Disneyland and Coca-Cola products, where mantras such as “fun/family/entertainment” and “Always Coca-Cola” are successfully employed respectively.The article strives to analyse and evaluate six major branding strategies, defining their advantages and disadvantages, namely (1) line brand strategy, (2) product-brand strategy, (3) endorsing brand strategy, (4) product assortment brand strategy, (5) umbrella brand strategy, and (6) source brand strategy. Theoretical generalisations are applied to practical situations with cases of the endorsing brand strategy for washing machines’ producers Bosch, Siemens, lndesit, Whirpool, AEG, Candy and Electrolux; the product assortment strategy for SELITA and RASA soft drinks; and the source brand strategy for KARŪNA chocolate bars.A considerate emphasis is placed on brand revitalisation, repositioning and rationalisation options, where examples of McDonald’s, Financial Times, Johnson & Johnson, Libella, Selita, Utenos alus, Ace Delicate, Obelių aliejus, Utenos sviestas, and Ragutis are being discussed and interpreted.The article concludes that an enterprise should select the most feasible strategy for their brands as well as acknowledge the necessity to revitalise, reposition or rationalise their brands according to the changes in the market and customers’ preferences.